Provides an optimization system for controlling input and output of materials in large industrial depots using the combination of image processing and RFID - Alidoost, Khaled (IJRDO -Journal of Computer Science Engineering, 2018)
The purpose of this research is to provide an optimization system for controlling the input and output of material (goods) in large industrial depots using thecombination of image processing and RFID. One of the practical applications of information technology in the industrial domain, and in particular intelligentsystems, is intelligent detection systems that control the exit of objects from the warehouse, which has many uses in order to mechanize the processes required to identify objects. Image processing and the system for detecting goods leaving the warehouse and detecting radio waves or RFIDs due to their proper  capabilities and the use of new technologies have a special place in intelligent material identification systems. Of course, along with the unique features of the above methods, each one has some irrefutable disadvantages. In this project, we tried to provide a combination of advantages of two methods of intelligent identification of objects in industrial warehouses such as RFID and image processing, which, with  the elimination of the disadvantages of the two methods, has a higher accuracy than each method.